2022
DOI: 10.3390/foods11182870
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Meat Analogues from Alternative Protein: A Systematic Literature Review

Abstract: This study aimed to conduct a systematic literature review (SLR) of the research performed in the plant-based meat analogues area. Historical, current, and future tendencies are discussed. The paper offers a comprehensive SLR coupled with a bibliometric analysis of the publication from 1972 to January 2022. The articles were obtained using a research string and precise inclusion and exclusion criteria from two prominent databases, Scopus and Web of Science (WoS). The Preferred Reporting Items for Systematic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 110 publications
0
28
0
Order By: Relevance
“…Thus, protein isolates are increasingly being replaced by protein concentrates (protein content between approx. 50 and 65%), without neglecting the structural properties required in the finished product [ 10 ]. These high-protein fractions are produced using dry separation processes.…”
Section: Production Technology Of Plant-based Meat Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, protein isolates are increasingly being replaced by protein concentrates (protein content between approx. 50 and 65%), without neglecting the structural properties required in the finished product [ 10 ]. These high-protein fractions are produced using dry separation processes.…”
Section: Production Technology Of Plant-based Meat Alternativesmentioning
confidence: 99%
“…The juiciness, tenderness, and other sensory attributes of meat-like products are also obtained by using fats/oils (such as coconut oil/butter, sunflower oil, canola oil, sesame oil, etc.). However, it is increasingly common to use binding agents (e.g., oleogels, starches, hydrocolloids, or fibers) as fat replacers [ 10 ]. Indeed, high amounts of fat—acting as a lubricant—could interfere with the protein denaturation process, which is the first kind of modification proteins need to undergo in order to obtain a meat-like structure.…”
Section: Production Technology Of Plant-based Meat Alternativesmentioning
confidence: 99%
“…The food system needs to change fundamentally to meet these challenges, and Fourth Industrial Revolution-enabled technologies, among others, will be a key component of this transformation. 1,2 The World Economic Forum's 2018 Innovation with a Purpose report found that healthcare has received cumulative start-up investments since 2010 that are ten times greater than those in the food industry, demonstrating that recent technological advancements have not been fully adopted by the food industry. In order to meet the dietary needs and food demands of a predicted population of 10 billion people by the middle of the century, alternative proteins that can replace conventional animal-based food are attracting significant financial investment, research focus, and media interest, though this does seem to be changing.…”
Section: Introductionmentioning
confidence: 99%
“…The world’s food systems will need to feed a population of more than 10 billion until 2050, who will be wealthier than people today and aspire to the kinds of food options currently found only in high income countries. This food must be produced ethically, considering both climate change and other environmental problems . Additionally, food has a greater impact on human health than any other factors; therefore, promoting healthy diets is crucial for everyone’s well-being as well as for containing the cost of medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A product with over 30% protein content (dry matter) and low-fat content is considered an excellent meat substitute [ 6 ]. It is also worth noting that substitutes or alternatives to meat products should be characterized by their similarity to meat protein digestibility-corrected amino acid score (PDCAAS) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%